2011
DOI: 10.1007/s11104-011-0926-4
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic translocation in rice investigated using radioactive 73As tracer

Abstract: Background and aims Excessive accumulation of arsenic (As) in rice (Oryza sativa L.) may pose a health risk to rice consumers. Long-distance transport of As within plant tissues is not well understood. The aim of our study was to evaluate As translocation from roots to shoots and from shoot tissues to rice grain. Methods At the grain filling stage, 73 As-labelled arsenite was fed to roots, cut stems or flag leaves of rice. The root-feeding experiment also included a treatment of steam girdling near the base of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(32 citation statements)
references
References 40 publications
4
28
0
Order By: Relevance
“…Thus, the companion cells possibly provide the most important storage capacity of As in rice aboveground tissues, implying that the biosynthesis of phytochelatins and the vacuolar transport of As(III)-phytochelatin complexes are likely to be much enhanced in this cell type. This distribution pattern also supports the notion that inorganic As is transported to the grain mainly via the phloem [40,41], although with a restricted mobility, presumably because of the vacuolar sequestration. In rice grain, information obtained largely through fluorescence tomography indicates that inorganic As [mainly As(III)] accumulates preferentially in the ovular vascular traces (OVTs) (Figure 2F), which are the conducting tissues transporting nutrients and water to the grain [42][43][44].…”
Section: Trends In Plant Sciencesupporting
confidence: 83%
See 1 more Smart Citation
“…Thus, the companion cells possibly provide the most important storage capacity of As in rice aboveground tissues, implying that the biosynthesis of phytochelatins and the vacuolar transport of As(III)-phytochelatin complexes are likely to be much enhanced in this cell type. This distribution pattern also supports the notion that inorganic As is transported to the grain mainly via the phloem [40,41], although with a restricted mobility, presumably because of the vacuolar sequestration. In rice grain, information obtained largely through fluorescence tomography indicates that inorganic As [mainly As(III)] accumulates preferentially in the ovular vascular traces (OVTs) (Figure 2F), which are the conducting tissues transporting nutrients and water to the grain [42][43][44].…”
Section: Trends In Plant Sciencesupporting
confidence: 83%
“…NanoSIMS has been used to reveal the uptake and competition between rhizosphere microorganisms and plant roots for 15 N labeled ammonium [55,56]. Pulsing cut stems of bean (Phaseolus vulgaris) plants with 26 Mg, 41 K, 44 Ca, and H 2 18 O and using cryo-SIMS to image their distribution at different times revealed a rapid exchange of cations between xylem vessels and the adjacent xylem parenchyma cells, and a slow exchange with cambium and phloem; the three cations also exhibited different exchange kinetics [57,58]. In these studies, samples were shock-frozen in melting propane, fractured, and analyzed under cryo-conditions, thus preserving the cellular structure and in situ element distribution.…”
Section: Trends In Plant Sciencementioning
confidence: 99%
“…Carey et al (2011) fed excised flag leaves with As(III), and found As in the flag leaf, while no As was detected in the grain. In contrast, Zhao et al (2012) exposed excised flag leaves to radioactive 73 As-labeled As(III) and found 2%-3% of the total absorbed As was transported to the grain. The different results between the studies were explained by the higher sensitivity of the 73 As method.…”
Section: As Species In Polished Ricementioning
confidence: 97%
“…As(III) transport into rice grain occurs nearly exclusively via the phloem, since the grain As level was reduced by 90% to 97% when phloem at the base of the panicle was destroyed (Carey et al, 2010;Zhao et al, 2012). As(III) may be loaded into the phloem in the leaves, especially the flag leaf, as well as in the stem nodes by xylem-to-phloem transfer.…”
Section: As Species In Polished Ricementioning
confidence: 99%
“…Wu et al 26 (2012) also showed that there was no significant difference between arsenite and arsenate treatments in As accumulation in rice roots. However, there was a significant difference in As accumulation in shoots between these two As treatments (P<0.001) and this may be due to different transportation mechanisms from root to shoot between arsenite and arsenate (Zhao et al, 2012) 48 . Aerated treatments showed significantly lower As accumulations in roots compared to stagnant treatments (Table 2).…”
Section: Disscussionmentioning
confidence: 88%